Bioastronomy 2007: molecules, microbes, and extraterrestrial life: proceedings of a workshop held at San Juan, Puerto Rico 16 - 20 July 2007 - Meech, Karen J. (Astronomical Society of the Pacific conference series, 2009)
Literaturangaben
Includes bibliographical references
Keywords: Konferenzschrift; Astrobiologie